Adolescent girls with asthma have worse asthma control and health‐related quality of life than boys—A population based study. Issue 7 (26th April 2017) - Stridsman, Caroline; Backman, Helena; Eklund, Britt‐Marie; Rönmark, Eva; Hedman, Linnea
Abstract: Background: Population‐based studies investigating health‐related quality of life (HRQoL) among asthmatic adolescents are rare. Further, among subjects with asthma, HRQoL may be affected by asthma control and severity. Aim: To investigate HRQoL in relation to asthma control and asthma severity among adolescents. Method: As a part of the population‐based OLIN pediatric study, 266 adolescents with current asthma (14‐15 yr) were identified. N = 247 completed the DISABKIDS HRQoL asthma module, including the domains impact and worry. The Asthma Control Test (ACT) was used and a disease severity score was calculated based on symptoms and medicine use. Results: The prevalence of current asthma was 11%. Well‐controlled asthma was reported by 15% of the adolescents, and 53% had partly controlled asthma. The prevalence of uncontrolled asthma was significantly higher among girls than boys (38% vs 25%), and girls also reported lower HRQoL scores. There was a fairly strong correlation between the ACT and DISABKIDS scores. Independent risk factors for low HRQoL impact (a score <67) were female sex (OR 4.66, 95%CI 1.82‐9.54) and decreased ACT scores (1.38, 1.18‐1.62). Risk factors for low HRQoL worry (a score <70) were female sex (3.33, 1.41‐7.86), decreased ACT scores (1.35, 1.16‐1.57), severe asthma (6.23, 1.46‐16.50), and having current eczema (2.68, 1.00‐7.24). Conclusion: Only a minority of the asthmatic adolescents reported well‐controlled asthma, and poor asthma control and female sex were risk factors for low HRQoL. Our results demonstrate that evaluation of asthma control is of great importance for asthma management.